Building the New Man - Francesco Cassata (Central European University Press, 2011)
Based on previously unexplored archival documentation, this book offers the first general overview of the history of Italian eugenics, not limited to the decades of Fascist regime, but instead ranging from the beginning of the 1900s to the first half of the 1970s. The Author discusses several fundamental themes of the comparative history of eugenics: the importance of the Latin eugenic model; the relationship between eugenics and fascism; the influence of Catholicism on the eugenic discourse...